The transcriptional activation domain of varicella-zoster virus open reading frame 62 protein is not conserved with its herpes simplex virus homolog. - Cohen, J I (1993)
Varicella-zoster virus (VZV) open reading frame 62 (ORF62) encodes an immediate-early protein that transactivates expression of VZV, herpes simplex virus (HSV), and cellular genes in transient expression assays. VZV ORF62 is homologous to HSV ICP4 and pseudorabies virus immediate-early (IE180) proteins. All three viral proteins have conserved DNA binding domains that recognize similar sites in their corresponding promoters. Here, we show that the transcriptional activation domain of ORF62 is located near the amino terminus of the protein and is not conserved with the activation domain of ICP4. A 161-amino-acid activation domain of ORF62 activates transcription to a level comparable to that of the potent HSV VP16 activation domain; much of the activity is contained in the first 90 amino acids of ORF62. Deletion of the activation domain from full-length ORF62 markedly reduced transactivating activity. These experiments indicate that while VZV ORF62 and HSV ICP4 have conserved amino acid sequences, including their DNA binding domains, the transcriptional activation domains are poorly conserved.